(untitled) (REMUNOM, 2024)
Public Research Institutions (PRIs) play a crucial role in national development; however, they face challenges in the face of political, economic, and social changes. This study proposes a technological forecasting model for PRIs, integrating innovation, costs, and market potential with Structural Equation Modeling. According to innovation laws, PRIs are tasked with contributing economically and socially through technological development. In a survey of 104 employees from three PRIs in Piauí, the proposed model demonstrates that technological forecasting mechanisms can influence cost analysis, innovation strategies, and market vision. Based on the questionnaires applied, the need for training in Intellectual Property and investments in Technology Innovation Centers was highlighted. These actions aim to improve Technology Transfer (TT) processes. It is observed that cost analysis, innovation strategies, and market vision support an appropriate evaluation and valuation of technologies.